Implementasi Kompensasi Berbasis Kinerja untuk Meningkatkan Motivasi Guru Honorer - Al-Qosam, Sayyid Naufal (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2024)
Compensation is a reward for services performed by someone. Compensation is given based on the terms of work performed. In the scope of education, a teacher will be given compensation for the performance he has carried out. However, compensation is different between permanent teachers and honorary teachers. The government regulates compensation for permanent teachers, while it depends on institutional regulations for honorary teachers. This is what makes providing compensation for honorary teachers often a problem. One of them is the absence of benchmarks for compensating honorary teachers. This paper discusses the challenges and opportunities in implementing performance-based compensation. The method used in this research is qualitative. The approach used is a literature study. Challenges found in implementing performance-based compensation include performance measurement, limited resources and teacher resistance. Meanwhile, the opportunities increase teacher motivation and improve the quality of education and professional development. Providing performance-based compensation has the potential to be a solution to reducing problems that occur with honorary teachers.